The Road to Sustained Growth in Jamaica. (World Bank country study., 2004)
"Jamaica's economic history is a story of paradoxes and potential. It has an English-speaking and a reasonably well-educated labor force, is close to the world's largest market, the United States, and has an abundance of natural beauty, which has spurred tourism. Many of its social and governance indicators are strong, including near universal school enrollment and poverty levels below that of comparable countries. However, the Jamaican story is marked by the paradoxes of low growth in GDP and high employment despite high investment and important achievements in poverty reduction. This paper attempts to explain these paradoxes and concludes that one possible explanation in that GDP has been understated."--Jacket